Transition metal doped aluminum clusters: an account of spin - Sengupta, Turbasu; Das, Susanta; Pal, Sourav (Journal of Physical Chemistry C, 2016)
The influence of spin on the properties of small sized transition metal doped aluminum clusters are investigated in the framework of density functional theory (DFT). Detailed analysis on minimum spin doped aluminum clusters has shown prominent indication of odd even oscillation in various calculated properties, supporting the presence of jellium shell structures within them. However, optimized high spin ground state counterparts, on the other hand, show rather smooth trends consistent with the properties of bulk materials. Resemblance to the bulk transition metals is further reflected in the gradual declining trends of heat of adsorption of CO2 molecule on cluster surface by sequentially changing the dopant atom from scandium to zinc. All the observations are also compared and found to be consistent with the earlier theoretical and experimental findings as obtained in the current literature. The similarities in the properties between atomic clusters and the bulk material is of utter importance and indeed precious considering the promising influence of the acquired information in understanding the process of evolution of nanoparticles from constituent atoms.